The Relationship Between Reading Anxiety, Vocabulary Mastery, and Reading Comprehension Among Senior High School Students - Nasution, Sahara Ani; Harahap, Tinur Rahmawati; Mahrani (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This study investigates the relationship between reading anxiety, vocabulary mastery, and reading comprehension among eleventh-grade students at SMA Negeri 1 Padangbolak Julu. Using a quantitative correlational design, data were collected through a reading comprehension test, a vocabulary mastery test, and a reading anxiety questionnaire. The results revealed a significant negative correlation between reading anxiety and reading comprehension, and a significant positive correlation between vocabulary mastery and reading comprehension. Moreover, a multiple regression analysis showed that reading anxiety and vocabulary mastery together significantly predicted reading comprehension, accounting for 26.8% of the variance. These findings suggest that both psychological and linguistic factors play essential roles in students’ reading performance. The study recommends that educators reduce students’ anxiety and enhance vocabulary instruction to improve reading outcomes.